Religijom preko dijaloga do međunacionalnog pomirenja i tranzicione pravde - Donev, Dejan (Centar za istraživanje religije, politike i društva, Novi Sad, 2013)
At the heart of all cultures and civilizations lies their religion that equally shaps them. From many methods to understand religion and its role in overall, especially in a particullar culture and history, as for example the culture of Balkan, one stands out for its importance – dialogue. His birthplace is the Balkans since the time of Socrates and his maieutics. It represents a radically new consciousness that profoundly changed the ways in which we understand the most comprehensive approach to life. This opens the door to an era of global dialogue as global dialogical way of understanding life unprocuring the same on a global religion, but drawing from it and leading to conscious acceptance of a common set of ethical principles that has a major role in inter-national reconciliation and transitional justice. Dialogue, according to the current catalog of conflicts in which religions, churches or ideologies are constituent elements, its basic function is to raise us into an era of global dialogue, and religions, churches and ideologies to facilitate faster to pass phase of transition, because they represent a key link in the chain without which reconciliation is simply impossible.
Based on religion through dialogue toward inter-national reconciliation and transitional justice
Keywords: Religion, Dialogue, Transitional Justice, Western Balkans